Modulation of NFKB1/p50 by ROS leads to impaired ATP production during MI compared to cardiac hypertrophy. Issue 2 (12th September 2017) - Mitra, Arkadeep; Datta, Ritwik; Rana, Santanu; Sarkar, Sagartirtha
Abstract : Pathological hypertrophy and myocardial infarction (MI) are two etiologically different cardiac disorders having differential molecular mechanisms of disease manifestation. However, no study has been conducted so far to analyze and compare the differential status of energy metabolism in these two disease forms. It was shown recently by our group that production of ATP is significantly impaired during MI along with inhibition of pyruvate dehydrogenase E1‐β (PDHE1 B) by pyruvate dehydrogenase kinase 4 (PDK4). However, the ATP levels showed no significant change during pathological hypertrophy compared to control group. To seek a plausible explanation of this phenomenon, the peroxisome proliferator‐activated receptor alpha (PPAR) pathway was studied in all the experimental groups which revealed that PGC1α‐ ERRα axis remains active in MI while the same remained inactive during pathological hypertrophy possibly by NF‐κB that plays a significant role in deactivating this pathway during hypertrophy. At the same time, it was observed that reactive oxygen species (ROS) negatively regulates NF‐κB activity during MI by oxidation of cysteine residues of p50‐ the DNA binding subunit of NF‐κB. Thus, this study reports for the first time, a possible mechanism for the differential status of energy metabolism during two etiologically different cardiac pathophysiological conditions involving PGC1α‐ERRα axis along with p50 subunit of NF‐κB. Abstract : Production of ATP is significantly impaired during MI along with inhibition of pyruvate dehydrogenase E1‐β (PDHE1 B) by pyruvate dehydrogenase kinase 4 (PDK4). ATP levels showed no significant change during pathological hypertrophy. NF‐κB plays a significant role in deactivating Peroxisome proliferator‐activated receptor alpha (PPAR) pathway during hypertrophy. Reactive oxygen species (ROS) negatively regulates NF‐κB activity during MI by oxidation of cysteine residues of p50‐ the DNA binding subunit of NF‐κB.